Rota-Viral Diarrhoea Progressing to Necrotizing Enterocolitis in Twin Neonates - Roy, Amrita; Dogra, Shivani; Chatterjee, Pallab; Chattopadhyay, Anindya (Journal of Nepal Paediatric Society, 2018)
We report late preterm twins who developed rota-viral diarrheal disease followed by necrotizing enterocolitis. Necrotizing enterocolitis had a fulminant course in both these neonates. Rota-viral infections in new-borns are reported to be mild or asymptomatic but in the above mentioned case, both the twins were severely affected leading to necrotizing enterocolitis. In the absence of risk factors, late preterm and term babies rarely develop Necrotizing Enterocolitis. We aim to highlight the importance of breast feeding through this case and also put forward the consideration for giving a birth dose of Rotaviral vaccination.